Influência da sombra do dossel temporário de um sistema agroflorestal na maturação de frutos de café - Leite, Paulo Henrique Marquezini (2021)
In Brazil, coffee trees have been included in agroforestry systems, mainly due to climatic emergencies and increased demand for specialty coffees. The shading levels inside a multi-layered agroforest depend on the design, management and, mainly, on the development time and evolution of the system. Understanding these variations over time, as well as the effects of temporary canopy on coffee production components, can contribute to the definition of more efficient agroforestry designs, especially in agroforestry systems (SAFs) in the establishment phase. In a four-year-old young agroforestry coffee plantation, in the process of stratification and establishment with a temporary canopy formed by Ricinus communis L., we aimed to evaluate the shading levels and its influence on the maturation of coffee (Coffea arabica L.) Bourbon amarelo . The shading was determined at four distances, at 1 m (D1), 4 m (D2), 7 m (D3) and 10 m (D4), from the sunniest edge (North face) to the interior of the SAF. We evaluated the shading levels, calculated by the difference of photosynthetically active radiation (PAR) in full sun and inside the SAF, quantifying the total volume of produced fruits, the percentage of dry fruits and the dry biomass of the coffee tree. As the distances from the edge to the interior of the SAF increased, the greater was the shading level. The evaluated coffee trees responded homogeneously within each distance, the more shaded ones produced a greater volume of fruits and a smaller percentage of them, dry. Coffee dry biomass was higher at distance D4. This work contributes to the understanding of how environmental factors, design and management of agroforestry influence the maturation of coffee fruits, a crucial factor for ordering the harvest and production of better quality coffees.